Understanding COUNTER 5 metrics in context: a case study on E-book vendor usage reports. Issue 3 (3rd July 2022) - Chen-Gaffey, Aiping; Getsay, Heather
Abstract: This study examines the effectiveness of the COUNTER 5 metrics relating to e-book usage reporting. Through three simulated processes on two major e-book platforms, EBSCOhost and ProQuest Ebook Central, the authors were able to gain insights into how usage was counted at item level within each e-book platform. The study finds that both vendors followed the principles of COUNTER 5 standard in usage reporting. Nevertheless, the result of data analysis also suggests that the difference in platform design between the two vendors had a direct impact on how usage was counted, thus affected the total outcome of e-book usage reports.